ANALYSIS OF THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON COMPANY VALUE WITH PROFITABILITY AS A VARIABLE MODERATION IN MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Sirait, Fransiska; Bukit, Rina; Bulan Siregar, Narumondang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine the effect of good corporate governance, namely the size of the board of commissioners, managerial ownership, institutional ownership, independent commissioners and risk management on firm value in manufacturing companies listed on the Indonesia Stock Exchange. In addition, this study also aims to determine whether profitability can be used as a moderating variable in the model.The research design is a causal relationship research with a quantitative approach. The sample in this study was 57 manufacturing companies listed on the IDX from 2016 to 2020. The type of data used in this study is secondary data. The sampling technique used was purposive sampling. And the data analysis technique used multiple linear regression analysis and interaction test (moderating) which was carried out with the help of SPSS software.The results in this study indicate that partially the size of the board of commissioners has no significant effect on firm value. Institutional ownership has a negative and significant effect on firm value. Managerial ownership, independent commissioners and risk management have a positive and significant impact on firm value. Meanwhile, profitability cannot moderate the size of the board of commissioners, institutional ownership, managerial ownership, independent commissioners and risk management on firm value in manufacturing companies listed on the Indonesia Stock Exchange.